Music Composition of Accompaniment for Fusion Dance 8 Ethnics of North Sumatera - Theodora Sinaga (Budapest International Research and Critics University, 2019)
This study aims to examine the process of creating musical accompaniment to dance composition and the function of music in a composition of dance works. This study is conducted by using qualitative descriptive method and systematic data analysis by using the concept of dance music creation theory to deepen and interpret data specifically, the answer are found that the process of creating a composition of dance accompaniment music with the theme of a combination of eight North Sumatra ethnic groups are as follows; 1) The creation process of the dance music is a process that involves intensely between dance stylists and dancers with music stylists along with music players, in adjusting between the gestures of the dancers and the form of music as a dance accompaniment. 2) Some important things done by the music stylist (composer) in the process of composing dance accompaniment music include; a) Conduct pre-composition, b) Perform initial composition, 3) Revise composition, 3) Perform final composition. 3) The function of music in dance works includes; a) Music functions in asserting movements in dance. b) Music functions as a marker in changing dance movements, c) Music functions as a marker of atmosphere in dance. d) Music functions to strengthen the emotions of dancer. e) Music functions to strengthen the picture of the atmosphere in parts of dance composition. f) Music functions to regulate the tempo, rhythm and dynamics of dance movements. g) Music functions to emphasize the accentuations of dance movements. h) Music functions as an introduction to the climax of dance work.